Does agricultural cooperative membership impact technical efficiency of maize production in Nigeria: an analysis correcting for biases from observed and unobserved attributes - Olagunju, K.O.; Ogunniyi, A.I.; Oyetunde-Usman, Z.; Omotayo, A.O.; Awotide, B.A. (Public Library of Science, 2021)
The formation of agricultural cooperatives has been widely promoted as an agricultural development policy initiative to help smallholder farmers cope with multiple production and marketing challenges. Using a nationally representative survey dataset of smallholder maize producers from rural Nigeria, this study assesses the impact of agricultural cooperative membership on technical efficiency (TE). We based our estimation approach on the combination of a newly developed sample selection stochastic production frontier model with propensity score matching to control for possible selectivity biases from both observables and unobservables. We estimate stochastic meta-frontiers to examine TE differences between cooperative members and non-members. Our results reveal that TE levels of members are consistently higher than that of non-members. This calls for continued policy incentives targeted at encouraging farmers to form as well as participate in agricultural cooperatives.